NILAI PATRIOTISME DALAM NOVEL KIDUNG DARI NEGERI APUNG KARYA ARSYAD SALAM DAN PEMANFAATANNYA SEBAGAI BAHAN PEMBELAJARAN SASTRA DI SMA - Soleha, Ana Fadhiatus; Priyadi, A. Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrackThe background of this research was to found out the value of patriotism in Kidung dari Negeri Apung Novel by Arsyad Salam. The method in this research was descriptive method in qualitative approach. The approach conducted in this research was literature sociology approach that focused on text sociology. The result in this result were: (1) the loyalty value to homewotn, including not forgetting about hometown, choose to back to hometown, developing physical and psychological, applied the developed things; (2) the courage element to save the hometown, including participated in build harmony and unity, implemented rights and obligations, carried the values; (3) the sacrificing element for hometown, including ready to sacrifice with whole body and soul, contributed in the development of prosperity, believe that the sacrifice is not meaningless; (4) the love element for hometown including know and understand about the circumstances, save and conserve the tradition, culture, and values, gave contribution through the improvement and prosperity for hometown. (5) an implementation plan had been developed about the value of patriotism in the novel for Indonesia language learning at Grade XII on High School.Key words: value, patriotism, novel